2021
DOI: 10.1101/2021.06.04.447049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mangrove forests mitigate coral bleaching under thermal stress from climate change

Abstract: Anthropogenic marine heatwaves are progressively degrading coral reef ecosystems worldwide via the process of coral bleaching (the expulsion of photosynthetic endosymbionts which reveals the coral skeleton). Corals from mangrove lagoons are hypothesised to increase resistance and resilience to coral bleaching, highlighting these areas as potential natural refuges for corals. Our study, the first conducted at a global-scale, reveals that coral reefs associated with mangrove forests are less likely to bleach und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Regional variation of bleaching responses to local stressors is unsurprising considering spatial variation in bleaching patterns (McClanahan et al., 2020; Sully et al., 2019). These spatial variations exist as a result of numerous factors, including local species composition (and pre‐disturbance cover), which is strongly influenced by disturbance history (Selig et al., 2012; Stuart‐Smith et al., 2018; Zhang et al., 2014), the biogeography and evolutionary history of regions (Osman et al., 2018), environmental conditions, such as turbidity (Cacciapaglia & Woesik, 2016; Sully & van Woesik, 2020), and connectivity between ecosystems (Johnson et al., 2021). Here, we highlight that local stressors incurred from local HPD may result in exacerbated bleaching severity in certain regions of the world, such as the Sunda Shelf (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional variation of bleaching responses to local stressors is unsurprising considering spatial variation in bleaching patterns (McClanahan et al., 2020; Sully et al., 2019). These spatial variations exist as a result of numerous factors, including local species composition (and pre‐disturbance cover), which is strongly influenced by disturbance history (Selig et al., 2012; Stuart‐Smith et al., 2018; Zhang et al., 2014), the biogeography and evolutionary history of regions (Osman et al., 2018), environmental conditions, such as turbidity (Cacciapaglia & Woesik, 2016; Sully & van Woesik, 2020), and connectivity between ecosystems (Johnson et al., 2021). Here, we highlight that local stressors incurred from local HPD may result in exacerbated bleaching severity in certain regions of the world, such as the Sunda Shelf (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Reef Check data are collected using established protocols to a high standard by citizen scientists, with the reliability reported in Done et al (2017) who found that the monitoring protocol has high accuracy, showing sampling error < ± 7% error for cover of benthic components. These data have also been utilized and described in previous macroecological studies (Bruno & Valdivia, 2016;Donovan et al, 2021;Johnson et al, 2021;Sully et al, 2019;Sully & van Woesik, 2020). From Reef Check data, coral bleaching (% of population) along with latitude-longitude geographic coordinates and the date of each survey were collected to allow for spatial extraction for HPD data.…”
Section: Introductionmentioning
confidence: 99%
“…Data are available from the Dryad Digital Repository: https://doi.org/10.5061/dryad.m905qfv5m (Johnson et al 2023). Code is available from Github: https://github.com/ JackVJohnson/Global_bleaching_mangroves.…”
Section: Author Contributionsmentioning
confidence: 99%